Functional characterization of ABCC9 variants identified in sudden unexpected natural death. (May 2019) - Subbotina, Ekaterina; Yang, Hua-Qian; Gando, Ivan; Williams, Nori; Sampson, Barbara A.; Tang, Yingying; Coetzee, William A.
Highlights: Channelopathies are often associated with inherited arrhythmias and sudden death. Genetic testing can assist in determining the likely causes of sudden unexpected death. We identified four ABCC9 variants in sudden unexpected death. All four variants caused a gain-of-function phenotype of KATP channels. Abstract: Background: Genetic variation in ion channel genes ('channelopathies') are often associated with inherited arrhythmias and sudden death. Genetic testing ('molecular autopsies') of channelopathy genes can be used to assist in determining the likely causes of sudden unexpected death. However, different in silico approaches can yield conflicting pathogenicity predictions and assessing their impact on ion channel function can assist in this regard. Methods and results: We performed genetic testing of cases of sudden expected death in the New York City metropolitan area and found four rare or novel variants in ABCC9, which codes for the regulatory SUR2 subunit of KATP channels. All were missense variants, causing amino acid changes in the protein. Three of the variants (A355S, M941V, and K1379Q) were in cases of infants less than six-months old and one (H1305Y) was in an adult. The predicted pathogenicities of the variants were conflicting. We have introduced these variants into a human SUR2A cDNA, which we coexpressed with the Kir6.2 pore-forming subunit in HEK-293 cells and subjected to patch clamp and biochemical assays. Each of the four variants led to gain-of-function phenotypes. The A355S and M941V variants increased in the overall patch current. The sensitivity of the KATP channels to inhibitory 'cytosolic' ATP was repressed for the M941V, H1305Y and K1379Q variants. None of the variants had any effect on the unitary KATP channel current or the surface expression of KATP channels, as determined with biotinylation assays, suggesting that all of the variants led to an enhanced open state. Conclusions: All four variants caused a gain-of-function phenotype. Given the expression of SUR2-containing KATP channels in the heart and specialized cardiac conduction, vascular smooth muscle and respiratory neurons, it is conceivable that electrical silencing of these cells may contribute to the vulnerability element, which is a component of the triple risk model of sudden explained death in infants. The gain-of-function phenotype of these ABCC9 variants should be considered when assessing their potential pathogenicity.